Quo Vadis Pengembangan Keilmuan UIN: Sekularisasi atau Quranisasi Ilmu Pengetahuan - Lukman Hakim (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
Abstract: The conversion of State Islamic Institute to State Islamic University triggers debate among intellectuals. Supporters of the conversion see the effort a way to islamize knowledge. While the opponents see it differently, the conversion would secularize knowledge. Starting from this point, this article closely studies the efforts of the Islamic University in developing the knowledge, would it be directed to either secularization or islamization one? To respond the question, this article offers as well as formulates the blueprint of modified knowledge development at the Islamic University that is based on the Quran. The blueprint is formulated through three main stages. Firstly, it positions Tauhid to be the foundation of the knowledge. Secondly, it formulates integrating curriculum that is based on Islamic knowledge and sciences. Lastly, it revitalizes the value of practicality into Islamic knowledge. The modified blueprint is expected to strengthen Islamic science that is based on the true Tauhid. At the same time, it offers responsibility in responding the future challenges.Abstrak: Transformasi status Institut Agama Islam Negeri menjadi Universitas Islam Negeri memunculkan pro dan kontra di kalangan intelektual. Intelektual yang pro dengan optimis memandang perubahan ini sebagai peluang islamisasi ilmu pengetahuan. Sedangkan kalangan yang kontra menilainya sebagai bagian dari upaya sekularisasi ilmu- ilmu keislaman. Berangkat dari pertentangan pendapat di atas maka makalah ini ingin mencermati ke mana arah pengembangan keilmuan UIN ini hendak dibawa? Apakah ia akan mengarah kepada sekularisasi ilmu pengetahuan atau sebaliknya akan terjadi qur‟anisasi ilmu pengetahuan? Untuk menjawab permasalahan di atas maka tulisan ini menarwarkan sekaligus memformulasikan rekayasa blue print pengembangan keilmuan UIN yang berbasis qur‟ani. Perancangan ini diformulasikan dalam tiga tahapan utama; meletakkan landasan keilmuan berbasis tauhid, memformulasikan kurikulum yang mengintergrasikan ilmu-ilmu keislaman dengan ilmu-ilmu umum, dan merevitalisasikan nilai-nilai praktis dalam pengembangan ilmu-ilmu keislaman. Rekayasa blueprint ini diharapkan menjadi formula penguatan sains Islam ke depan dengan landasan tauhid yang benar sekaligus memiliki responsibilitas dalam menjawab tantangan masa depan.